Sustainable finance, SDG’s & role of accounting student - Derry Wanta; Hasri Nirmala (Privietlab, 2021)
The Sustainable Development Goals (SDGs) are an international agenda that is a continuation of the Millennium Development Goals (MDGs). The SDGs were compiled by the United Nations (UN) involving 194 countries, civil society, and various economic actors from all over the world. This agenda was created to answer the demands of world leadership in overcoming poverty, inequality, and climate change in the form of concrete actions. The SDGs were set on September 25, 2015 and consist of 17 (seventeen) global goals with 169 (one hundred and sixty nine) targets that will serve as policy and funding guidelines for the next 15 years and are expected to be achieved by 2030. These goals and targets include: 3 (three) dimensions of sustainable development, namely environmental, social, and economic. Since the issuance of Presidential Regulation No. 59 of 2017 concerning the Implementation of Achieving Sustainable Development Goals, the implementation and success of the SDGs has involved many parties and academics, one of which is. The webinar was attended by 265 people via zoom media. Webinar participants came from UNSADA and Non-UNSADA circles consisting of various agencies such as Students, Workers, Students from Universities in Eastern Indonesia and civil servants. This webinar received positive feedback from participants based on the online sheets received. In general, participants welcomed this webinar.